Development of Social Emotional Competency Assessment Instruments: Proof of Conten Validity and Inter-Rater Reliability - Sri Rejeki Setiyorini; Wiwi Isnaeni; Saiful Ridlo (Journal of Research and Educational Research Evaluation, 2025)
Social Emotional Competence (SEC) was one of the components of 21st-century education that was considered very important for students in preparing for future needs and challenges. The number of SEC assessment instruments was limited; therefore, it was necessary to develop SEC assessment instruments. An instrument had to be tested for validity and reliability before being used, so validity and reliability testing were crucial during the development process. This study aimed to test the content validity and inter-rater reliability of the developed SEC instrument. The study was a type of Research and Development (R&D). Content validity analysis used Aiken’s V, while reliability was analyzed using the Ebel formula. The results of the content validity based on assessments from 5 experts showed that the average Aiken’s V value was 0.847, which indicated a coefficient value > 0.80. Inter-rater reliability, analyzed using the Ebel formula, yielded a reliability coefficient value of 0.962. These findings proved that the SEC assessment instrument for students was valid and reliable and could be used for field testing.